The Musical Orchestra Leadership: An Imagery of Participative and Relational Societal Leadership Style - ODUNUGA, Adeola Funmilayo; Yekini-Ajenifuja, Isaac A. (Advances in Social Sciences Research Journal, 2022)
The issue of leadership in society has been of major concern from times immemorial, this is because it is believed that the quality of leadership is one of the major determinants of societal development. The existing societal leadership style in Nigeria seems not to help the populace in meeting societal needs and satisfying human aspirations, hence there is a need for an improved leadership style that will help in the attainment of societal and individual goals. Using existing leadership theories, this paper explains the ideals of a good participative and relational leadership style using metaphoric inference of an orchestra and its conductor. The study is an ethnographic study that used oral interviews and other qualitative techniques to obtain its information. The research discovered that with a competent leader (conductor) at the head of a team of members (the orchestra), society is capable of doing great as long as everyone does their specific roles. Societies will fare well if the ideas of this imagery are adopted. The paper recommends that the younger generation should be encouraged to learn and adopt participative and relational leadership styles.